2020
DOI: 10.3892/ol.2020.11358
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin is an efficient predictor of neck lymph node metastasis in tongue squamous cell carcinoma with low tumor budding grade

Abstract: The current study investigated the efficacy of podoplanin expression in tumor budding cells as a predictor of neck lymph node metastasis (NLM) in patients with tongue squamous cell carcinoma (SCC) of low tumor budding grade (TBG). A total of 99 patients with early T-stage tongue SCC of any clinical N status who received the initial curative treatment were enrolled. The association between podoplanin expression and NLM was immunohistochemically analyzed, with a focus on tongue SCC with low TBG. The disease-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…Four studies 25,27–29 on tumor budding reported statistical values for overall survival (OS) including HRs and 95% CI. These studies were included in the meta‐analysis and are presented using a forest plot (Figure 2A) with results from multivariate analysis of the relevant studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies 25,27–29 on tumor budding reported statistical values for overall survival (OS) including HRs and 95% CI. These studies were included in the meta‐analysis and are presented using a forest plot (Figure 2A) with results from multivariate analysis of the relevant studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the emerging prognostic markers that are not included in the pathology report, the published studies revealed a promising prognostic value for cancer‐related histopathologic markers including cell‐in‐cell structures (one study), 19 tumor budding (seven studies), 13,15,25–29 and pattern of invasion (15 studies) which were evaluated either as mode of invasion, 22,30 pattern of invasion, 31–34 invasive pattern, 28 or WPOI 13,16,25,35–39 . At the same time, some of the relevant studies analyzed stromal‐related histopathologic markers including stromal infiltrating lymphocytes (one study) 18 and tumor–stroma ratio (TSR; three studies) 17,40,41 which were significantly associated with prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of PDPN, a small mucin-like type-1 transmembrane protein and a speci c marker for lymph vessel endothelial cells [43], signi cantly increased endothelial cell adhesion, migration, and tube formation, whereas inhibition of PDPN expression decreased dermal lymphatic endothelial cell adhesion [44]. PDPN is a speci c marker for the lymphatic endothelium in histopathology [45].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical expression patterns of pan-cytokeratin and podoplanin were reported to be an effective predictor of late cervical lymph node metastasis of TSCC. 25 A 2004 study attempted to predict late cervical lymph node metastasis by detecting vessels. 26 Such research requires complicated methods (e.g., immunostaining or speci c staining), whereas only the common tissue stain hematoxylin-eosin was the only method needed in the present study.…”
Section: Discussionmentioning
confidence: 99%